Institutionalizing Public Health Lessons from COVID-19 - Sarmast , Bahram (Health Nexus, 2025)
The COVID-19 pandemic revealed critical vulnerabilities in global and national public health systems, underscoring the urgent need to institutionalize lessons learned to enhance preparedness, equity, and resilience. This letter highlights key domains where reactive measures during the pandemic should now evolve into permanent, structured policy frameworks. These include embedding transparent communication protocols, formalizing community-level health governance, integrating mental health and equity considerations, and ensuring sustained global cooperation. Case examples demonstrate that institutional memory and participatory governance significantly enhance responsiveness during crises. Furthermore, the necessity of legal and structural mechanisms—such as mandatory After-Action Reviews (AARs), health security integration into development planning, and codified global vaccine equity frameworks—is emphasized as essential for long-term pandemic resilience. Rather than treating COVID-19 as an isolated event, policymakers must seize the opportunity to create enduring reforms that institutionalize best practices and protect populations from future public health emergencies.